Antagonist muscle co-contraction during a double-leg landing maneuver at two heights. Issue 13 (3rd October 2017) - Mokhtarzadeh, Hossein; Yeow, Chen Hua; Goh, James Cho Hong; Oetomo, Denny; Ewing, Katie; Lee, Peter Vee Sin
Abstract: Background: Knee injuries are common during landing activities. Greater landing height increases peak ground reaction forces (GRFs) and loading at the knee joint. As major muscles to stabilize the knee joint, Quadriceps and Hamstring muscles provide internal forces to attenuate the excessive GRF. Despite the number of investigations on the importance of muscle function during landing, the role of landing height on these muscles forces using modeling during landing is not fully investigated.Methods: Participant-specific musculoskeletal models were developed using experimental motion analysis data consisting of anatomic joint motions and GRF from eight male participants performing double-leg drop landing from 30 and 60 cm. Muscle forces were calculated in OpenSim and their differences were analyzed at the instances of high risk during landing i.e. peak GRF for both heights.Results: The maximum knee flexion angle and moments were found significantly higher from a double-leg landing at 60 cm compared to 30 cm. The results showed elevated GRF, and mean muscle forces during landing. At peak GRF, only quadriceps showed significantly greater forces at 60 cm. Hamstring muscle forces did not significantly change at 60 cm compared to 30 cm.Conclusions: Quadriceps and hamstring muscle forces changed at different heights. Since hamstring forces were similar in both landing heights, this could lead to an imbalance between the antagonist muscles, potentially placing the knee at risk of injury if combined with small flexion angles that was not observed at peak GRF in our study. Thus, enhanced neuromuscular training programs strengthening the hamstrings may be required to address this imbalance. These findings may contribute to enhance neuromuscular training programs to prevent knee injuries during landing.